2018
DOI: 10.1534/genetics.118.300807
|View full text |Cite
|
Sign up to set email alerts
|

MIB-1 Is Required for Spermatogenesis and Facilitates LIN-12 and GLP-1 Activity inCaenorhabditis elegans

Abstract: Covalent attachment of ubiquitin to substrate proteins changes their function or marks them for proteolysis, and the specificity of ubiquitin attachment is mediated by the numerous E3 ligases encoded by animals. Mind Bomb is an essential E3 ligase during Notch pathway signaling in insects and vertebrates. While encodes a Mind Bomb homolog (), it has never been recovered in the extensive Notch suppressor/enhancer screens that have identified numerous pathway components. Here, we show that null mutants have a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 116 publications
1
9
0
Order By: Relevance
“…Similar to our findings, Ratliff et al (2018) showed that GFP::MIB-1 localized diffusely in the male germline, but not in sperm. In addition, they found that mib-1 has a function in the Delta/Notch pathway, as loss-of-function alleles of mib-1 partially suppressed gain-of-function lin-12 vulva developmental defects ( Ratliff et al 2018 ). Finally, Ratliff et al (2018) showed that MIB-1 can ubiquitinate itself in vitro .…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Similar to our findings, Ratliff et al (2018) showed that GFP::MIB-1 localized diffusely in the male germline, but not in sperm. In addition, they found that mib-1 has a function in the Delta/Notch pathway, as loss-of-function alleles of mib-1 partially suppressed gain-of-function lin-12 vulva developmental defects ( Ratliff et al 2018 ). Finally, Ratliff et al (2018) showed that MIB-1 can ubiquitinate itself in vitro .…”
Section: Resultssupporting
confidence: 92%
“…A phenotypic analysis of spe-16 showed that it had the same temperature-dependent, male-sterile phenotype as previously reported for fer-2 and -4 ( Ratliff et al 2018 ), but whether spe-16 disrupts the formation of the sperm nuclear halo was not tested. Similar to our findings, Ratliff et al (2018) showed that GFP::MIB-1 localized diffusely in the male germline, but not in sperm. In addition, they found that mib-1 has a function in the Delta/Notch pathway, as loss-of-function alleles of mib-1 partially suppressed gain-of-function lin-12 vulva developmental defects ( Ratliff et al 2018 ).…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations